Dual HLA B*42 and B*81-reactive T cell receptors recognize more diverse HIV-1 Gag escape variants. Issue 1 (December 2018) - Ogunshola, Funsho; Anmole, Gursev; Miller, Rachel; Goering, Emily; Nkosi, Thandeka; Muema, Daniel; Mann, Jaclyn; Ismail, Nasreen; Chopera, Denis; Ndung'u, Thumbi; Brockman, Mark; Ndhlovu, Zaza M
Abstract Some closely related human leukocyte antigen (HLA) alleles are associated with variable clinical outcomes following HIV-1 infection despite presenting the same viral epitopes. Mechanisms underlying these differences remain unclear but may be due to intrinsic characteristics of the HLA alleles or responding T cell repertoires. Here we examine CD8+ T cell responses against the immunodominant HIV-1 Gag epitope TL9 (TPQDLNTML180–188 ) in the context of the protective allele B*81:01 and the less protective allele B*42:01. We observe a population of dual-reactive T cells that recognize TL9 presented by both B*81:01 and B*42:01 in individuals lacking one allele. The presence of dual-reactive T cells is associated with lower plasma viremia, suggesting a clinical benefit. In B*42:01 expressing individuals, the dual-reactive phenotype defines public T cell receptor (TCR) clones that recognize a wider range of TL9 escape variants, consistent with enhanced control of viral infection through containment of HIV-1 sequence adaptation. Closely related HLA alleles presenting similar HIV-1 epitopes can be associated with variable clinical outcome. Here the authors report their findings on CD8+ T cell responses to the HIV-1 Gag-p24 TL9 immunodominant epitope in the context of closely related protective and less protective HLA alleles, and their differential effect on viral control